Tolerance induction in memory CD4 T cells requires two rounds of antigen-specific activation - David, Alexandria (National Academy of Sciences, 2014)
A major goal for immunotherapy is to tolerize the immune cells that coordinate tissue damage in autoimmune and alloantigen responses. CD4 T cells play a central role in many of these conditions and improved antigen-specific regulation or removal of these cells could revolutionize current treatments. A confounding factor is that little is known about whether and how tolerance is induced in memory CD4 T cells. We used MHC class II tetramers to track and analyze a population of endogenous antigen-specific memory CD4 T cells exposed to soluble peptide in the absence of adjuvant. We found that such memory T cells proliferated and reentered the memory pool apparently unperturbed by the incomplete activation signals provided by the peptide. Upon further restimulation in vivo, CD4 memory T cells that had been previously exposed to peptide proliferated, provided help to primary responding B cells, and migrated to inflamed sites. However, these reactivated memory cells failed to survive. The reduction in T-cell number was marked by low expression of the antiapoptotic molecule B cell lymphoma 2 (Bcl2) and increased expression of activated caspase molecules. Consequently, these cells failed to sustain a delayed-type hypersensitivity response. Moreover, following two separate exposures to soluble antigen, no T-cell recall response and no helper activity for B cells could be detected. These results suggest that the induction of tolerance in memory CD4 T cells is possible but that deletion and permanent removal of the antigen-specific T cells requires reactivation following exposure to the tolerogenic antigen.